1997
DOI: 10.1007/s001250050741
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and diabetes mellitus: is it time for intervention trials?

Abstract: During the past decade, the potential role of haemostatic factors, particularly fibrinogen, in atherosclerosis and its complications has gained considerable interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
1
27
1
1
Order By: Relevance
“…Fibrinogen is considered to be an indicator of inflammation, which is now widely accepted as a contributory factor in the development of atherosclerosis. Alternatively, fibrinogen may be directly involved in atherosclerosis and thrombosis, since hyperfibrinogenaemia leads to enhanced coagulant activity and is associated with increased blood viscosity [33]. Our findings suggest that in diabetic subjects, this relatively inexpensive test may be useful in the identification of high-risk subjects.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Fibrinogen is considered to be an indicator of inflammation, which is now widely accepted as a contributory factor in the development of atherosclerosis. Alternatively, fibrinogen may be directly involved in atherosclerosis and thrombosis, since hyperfibrinogenaemia leads to enhanced coagulant activity and is associated with increased blood viscosity [33]. Our findings suggest that in diabetic subjects, this relatively inexpensive test may be useful in the identification of high-risk subjects.…”
Section: Discussionmentioning
confidence: 83%
“…In diabetic subjects with plasma fibrinogen levels >4.1 g/l and macroalbuminuria, the risk of cardiovascular mortality is almost four times higher than that in normoalbuminuric subjects with plasma fibrinogen levels <3.0 g/l. Lifestyle modifications [34] and drugs, such as bezafibrate [33], have been found to reduce fibrinogen levels, though not selectively, which prevents assessment of the effect of its reduction in intervention trials.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that high plasma fibrinogen levels represent an independent marker for cardiovascular morbidity in both non-diabetic [5] and diabetic [6] subjects. Diabetic subjects have higher fibrinogen levels than the general population [7], but the data on subjects with IGT are contradictory [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by studies which found an increased ratio between fibrinogen and antithrombin III, due to a decrease in antithrombin III, in the aorta of diabetic rats [32] and the observation of increased levels of markers of thrombin activation in diabetic patients [33]. As recently suggested, this last condition may produce an increase in fibrinogen [34], a well recognized cardiovascular risk factor also in diabetes [35]. The fall in endothelial cell HS contents might also influence local fibrinolysis.…”
Section: Gags Microalbuminuria Diabetic Nephropathy and Cardiovascumentioning
confidence: 66%
“…An increasing number of studies are showing that the administration of GAGs lowers fibrinogen levels, the relevance of which as a cardiovascular risk factor in diabetes has already been stressed [35]. In particular, the fibrinogen reducing activity of sulodexide was demonstrated in hyperlipidaemic subjects [38] and in pilot studies in diabetic patients [25,39].…”
Section: Perspectivesmentioning
confidence: 99%